Extração e transesterificação do óleo de resíduo industrial de palmiste usando metanol supercrítico - COSTA, Wanessa Almeida da (Universidade Federal do Pará, 2019)
Palm kernel is an oleaginous seed found in fruits of Elaeis guineensis Jacq. and which represents one of the main oils consumed in the world, with an mean production of 18,59 million tons. Its main process is the extraction by mechanical pressing that generates, in the world, approximately 9.6 x 109 tons of residue also called residual cake. Since this residue can still present about 12% of remaining oil, supercritical fluid extraction (SFE) is presented as an alternative to the recovery of this oil. Soxhlet extraction was also performed to be compared to the SFE. Pressures of 150, 250 and 350 bar and temperatures of 40, 60 and 80 °C were used in the experiments. The raw material was characterized before and after the SFE by moisture, ash, fibers, proteins and lipids contents and the extracts were characterized by gas chromatography/mass spectrometry (GC/MS). The kinetic data were compared to the Sovová (2012) model and the condition of highest yield was used in the transesterification experiments. Molar ratios of 1:24 and 1:42 (oil: methanol), temperatures of 250, 300 and 350 °C, constant pressure of 200 bar and reaction times of 5, 10, 15, 20 and 25 minutes were used. The products were also analyzed by GC/MS to verify the transformation of triacylglycerols into methyl esters. The main results of this study were: SFE does not alter the centesimal composition of the raw material; the condition of highest yield was 350 bar and 80 °C; Sovová's model had the best fit to the kinetic data; the condition 1:42, 350 ºC was the one that obtained the highest content of esters (99.81%) in only 5 minutes of reaction. The transesterification of palm kernel oil in a supercritical medium is a valid alternative and presents advantages over the conventional method, however a more in-depth analysis considering the technical and economic limitations of this method is necessary.